2002
DOI: 10.1055/s-2002-35098
|View full text |Cite
|
Sign up to set email alerts
|

Easy Venous Superdrainage in DIEP Flap Breast Reconstruction Through the Intercostal Branch

Abstract: The deep inferior epigastric perforator (DIEP) flap has been shown to be a valid option for breast reconstruction, as it has certain advantages over the free TRAM flap, including lower morbidity in the donor area, conservation of abdominal wall function, and reduced postoperative pain. However, some cases of venous congestion in using the DIEP flap have been described. The authors present a case in which the venous return in a DIEP flap objectively (by measurement with a flux meter) presented a marked improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 5 publications
0
35
0
1
Order By: Relevance
“…The suggestion has been that there is individual variability in the dominance of these venous systems. Reported methods for maximizing venous drainage in this setting has been to augment the venous drainage of congested flaps through additional venae comitantes of the ipsilateral DIEA (Marck et al, 1996;Tutor et al, 2002), through venae comitantes of the contralateral DIEA (Niranjan et al, 2001), through venae comitantes of the ipsilateral SIEA (Villafane et al, 1999;Blondeel et al, 2000;Wechselberger et al, 2001), and one study has suggested the use of the venae comitantes of the contralateral SIEA (Lundberg and Mark, 2006).…”
Section: Venous Drainage Of the Anterior Abdominal Wallmentioning
confidence: 99%
“…The suggestion has been that there is individual variability in the dominance of these venous systems. Reported methods for maximizing venous drainage in this setting has been to augment the venous drainage of congested flaps through additional venae comitantes of the ipsilateral DIEA (Marck et al, 1996;Tutor et al, 2002), through venae comitantes of the contralateral DIEA (Niranjan et al, 2001), through venae comitantes of the ipsilateral SIEA (Villafane et al, 1999;Blondeel et al, 2000;Wechselberger et al, 2001), and one study has suggested the use of the venae comitantes of the contralateral SIEA (Lundberg and Mark, 2006).…”
Section: Venous Drainage Of the Anterior Abdominal Wallmentioning
confidence: 99%
“…To cope with this complication, superdrainage using the superficial epigastric vein has been proven effective [6][7][8][9][10][11]. We estimated the diameter of the vessel through MDCT preoperatively, and we preserved every perforator and pedicle, including all DIEAs, DIEVs, SIEVs, and superficial inferior epigastric arteries during dissection of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Niranjan et al describe using a vein graft to connect the DIEV to the cephalic vein [18]. Another option described by Tutor et al involved connecting a venae comitantes of the DIEP pedicle to an intercostal branch of the IMV [19]. Additionally, with routine harvest of a superficial vein, the superficial venous system may be used for venous augmentation of the congested DIEP flap.…”
Section: Discussionmentioning
confidence: 99%